A methodological framework for evaluating ADAS training for older drivers: Feasibility and user perception - Pełka, Małgorzata; Rodak, Aleksandra (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The rapid introduction of Advanced Driver Assistance Systems (ADAS) poses a unique challenge for older drivers, who often face barriers in adopting these technologies. This study evaluates the effectiveness of a practical, simulator-based training concept designed specifically for drivers aged 50+. The empirical analysis of a research group of 25 people focused on verifying four research hypotheses regarding the suitability of the simulator, trust calibration, user awareness, and training utility. The results confirmed that the high-fidelity simulator is an appropriate training environment for this demographic; analysis of the Revised Simulator Sickness Questionnaire (RSSQ) revealed a statistically significant reduction in symptoms during the adaptation process, validating the physical feasibility of the training (H1). The intervention led to a measurable increase in trust towards ADAS, with a strong effect size, confirming positive behavioral adaptation (H2). Furthermore, participants demonstrated raised awareness of system benefits, primarily identifying enhanced safety and speed control (H3). The proposed training model achieved high internal consistency and received positive subjective usability ratings (H4). These findings support the deployment of simulatorbased practical training as an effective tool for preventing digital exclusion among older drivers. Key words: driver training; ADAS; simulation sickness; older drivers; trust calibration.